Evaluation of the Effects of Orthopedic Treatment on the Dentofacial Structure and Upper Airway of Subjects with Skeletal Class III Malocclusion - Hilal Kan; Tevfik Sözen; Oğuz Öğretmenoğlu; Semra Ciğer (Galenos Yayinevi, 2024)
Objective: The present study aimed to evaluate the effect of rapid maxillary expansion (RME) and face mask treatment on the upper airway in patients with maxillary retrusion in two dimensions using digital cephalograms and volumetric evaluation using acoustic rhinometric measurements. Methods: A total of 22 individuals with a concave profile and skeletal and dental Class III malocclusion during growth and development with a mean age of 9.9±1.38 years were included in the study. A bonded RME appliance and a petit face mask were adapted for the patients. Before treatment (T0) and after maxillary protraction (T1), lateral cephalometric films and acoustic rhinometric recordings were obtained. The dependent sample t-test was used for statistical evaluation. Results: Cephalometric analysis revealed forward movement of the maxilla and backward downward rotation of the mandible. A significant increase was observed in the nasopharyngeal and oropharyngeal regions of the upper airway. Three-dimensional evaluation of the upper airway by acoustic rhinometry revealed only an increase in the volumes of the left nasal cavity after decongestant administration. A statistically significant increase in acoustic rhinometric measurements in nasal valves. When the correlation of the cephalometric findings of the nasopharyngeal region with the acoustic rhinometry findings was examined, no statistically significant relationship was found. Conclusion: As a result of this study, we observed an increase in the cephalometric measurements of the nasopharyngeal and oropharyngeal areas. A significant increase was observed in the minimal cross-sectional area measured by acoustic rhinometry.